A Study on The Mechanical Properties of Concrete Containing Fly Ash as Partial Cement Replacement-A Critical Review - azan, Ezzat Haziq; Hakim, Seyed Jalaluddin (Recent Trends in Civil Engineering and Built Environment, 2021)
Concrete has a considerable environmental impact. The demand for concrete is growing on a regular basis day and cement is used to fulfil the need for creation of infrastructure facilities. Portland cement is a high-energy material that requires a lot of heat to manufacture. In addition, the manufacture of this material includes the burning of limestone, and each tone of Portland cement emits almost one tone of CO2 into the atmosphere and can affect the environment. The conservation of cement is the most significant step in reducing both energy utilization and greenhouse gas emission. In order to reduce the amount of Ordinary Portland Cement (OPC) and CO2 emission, the past few decades geopolymers concrete has researched as a sustainable construction material, which they can reduce CO2 emission for its use by industry. Fly ash is considered as a geopolymer material in this study. Many studies have been conducted by researchers over the last few decades on the use of new materials in concrete to reduce the impact of cement and increase the compressive strength and workability of concrete. In this study, a critical review of the mechanical properties of concrete containing fly ash as a partial replacement for cement is carried out in order to provide recommendations. The methodology and results of the previous studies are summarized and some advantages and disadvantages of their works have been highlighted.